Role of Failure to Forgive Self, Others and Uncontrollable Situations in Predicting Depression Among the Elderly - Mohammad Ebrahimi; Manoochehr Azkhosh; Mahshid Foroughan; Behrouz Dolatshahi; Fatima Shoaai (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives Elderly people experience many resentments and the inability to forgive these resentments may be associated with depressive symptoms. Hence, we aimed to examine the relationships between forgiveness of self, others and uncontrollable situations with depression in the elderly. Methods & Materials In this cross-sectional study, 96 elderly of Jahandidegan Centers in Tehran City were enrolled using convenient sampling. They completed Heartland Forgiveness Scale (HFS) and Geriatric Depression Scale (GDS). Data were analyzed using Pearson correlation and multivariate regression through stepwise method. Results There was a negative and meaningful relationship between forgiveness of self (r=-0.32, P<0.01), forgiveness of others (r=-0.25, P<0.05) and forgiveness of uncontrollable situations (r=-.38, P<0.01) with depression in the elderly. Also forgiveness of uncontrollable situations (β=-0.33) and forgiveness of self (β=-0.26) have a more determining role in predicting depression (P<0.01). Conclusion Inability to forgive is associated with psychological vulnerability among the elderly; so, it is recommended that therapeutic models of enhancing forgiveness to be considered for the emotional problems of elderly people